Triorchidism: which therapy? - Eugenia Piro; Laura Abati; Veronica Zocca; Marta Brugnoni; Antonio D'Alessio (PAGEPress Publications, 2017)
Polyorchidism is an anomaly characterized by more than two gonads; triorchidism is the most common variant. Its management is controversial, mostly when surgical treatment is occasional. CB, 14 year-old, came to the hospital due to right-sided testicular torsion. During surgery, testis was rotated and the contralateral testis, which presented as an anatomically continuum with a gonadic structure similar to the other testes but with a smaller diameter, was fixed. We performed biopsy on both left testes and decided to preserve the supernumerary one. Following the anatomic and functional classification of polyorchidism by Singer, preservation is justified on the grounds of the presence of a supernumerary testis that drains into the epididymis of the normal testis, merging into one single deferent duct (Singer Type 1). At biopsy, both testes had a valid spermatogenic asset. The diagnostic follow-up at 6 and 12 months did not show any pathological alteration. Diagnosis of polyorchidism is occasional. Its treatment varies depending on the site, dimension, and anatomy of the drainage system of the supernumerary testis. If the supernumerary testis is preserved, a standardized diagnostic follow-up is recommended.